2022
DOI: 10.1111/1744-7917.13037
|View full text |Cite
|
Sign up to set email alerts
|

Relative contribution of genetic and environmental factors to determination of wing morphs of the brown planthopper Nilaparvata lugens

Abstract: Wing dimorphism is a fascinating feature of the ability of insects to adapt to environments. The brown planthopper (BPH) Nilaparvata lugens, a serious pest of rice, can switch between the long-and short-winged morphs. It has been known that environmental factors can affect the wing morph of BPH. However, it is still unclear whether the effect of environment is dependent on BPH genetic backgrounds or not. In the present study, we established the pure-bred lineages of short-and long-winged BPHs via multigenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…So, all these short‐winged morphs used in this study were the offspring of immigrated long‐winged morphs. A previous study also found that the pure‐bred lineage of the short‐winged morph of brown planthoppers was easier attained by artificial selection than that of the long‐winged morph (Zhang et al 2023). In this study, we found that the fecundity of the short‐winged strain increased as selection generation was increased, and the long‐winged strain did not change.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…So, all these short‐winged morphs used in this study were the offspring of immigrated long‐winged morphs. A previous study also found that the pure‐bred lineage of the short‐winged morph of brown planthoppers was easier attained by artificial selection than that of the long‐winged morph (Zhang et al 2023). In this study, we found that the fecundity of the short‐winged strain increased as selection generation was increased, and the long‐winged strain did not change.…”
Section: Discussionmentioning
confidence: 90%
“…The full-winged and vestigial-winged ecotypes of Zelandoperla fenestrata exhibited obvious assortative mating, and almost all vestigial-winged males attempted to mate with the vestigial-winged females and no full-winged males attempted to mate with the vestigial-winged females, which facilitates rapid ecological speciation of vestigial and full-winged ecotypes (Kroos et al 2021). Assortative mating between long-and short-winged adults is not obvious or does not exist in the wild populations of the rice planthopper (Oh 1979, Peng et al 2012, Zhang et al 2023), but in this study, we found when populations were purified in wing morph, the trend towards assortative mating occurred in the short-winged strain. The short-winged males copulated with short-winged females more successfully than that with the long-winged females.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this polyphenism has a rather complex genetic background. The different genotypes co-existing in both N. lugens and S. furcifera are not equally sensitive to the above mentioned environmental cues (MATSAMURA, 1996;IWANAGA et al, 1986;ZHANG et al, 2022). As most genetic studies have been carried out in Japan and China, where the populations are consisted of a mixture of immigrants from different southern source populations (IWANAGA et al, 1986), it is still not clear how much relevant genetic variation exist within and between the self-sustaining tropical and subtropical populations.…”
Section: Case Study I: Maintenance Of the Wing Dimorphic Rice Plantho...mentioning
confidence: 99%
“…This knowledge is at the moment still very scarce, and available only in a few selected "model" species: like the pea and aphid cotton aphids (Acyrthosiphon pisum Harris 1776, Aphis gossypii Glover 1877) and the rice planthoppers Nilaparvata lugens and Sogatella furcifera. However, exponential growth is expectable also in this area of research, and a synthesis of all aspects of wing polymorphism will be possible then (OGAWA et al, 2012;OGAWA and MIURA, 2014;YU et al, 2014;JI et al, 2021;ZHANG et al, 2022;). Some of the wing dimorphic and polymorphic insects are serious agricultural pests, like many species of aphids and planthoppers on many different crops, or the oriental chinch bug (Cavelerius saccharivorus Okajima, 1922) on sugarcane (FUJISAKI, 1989).…”
Section: Introductionmentioning
confidence: 99%